DILEMA NIKAH SIRI: ANTARA HUKUM ISLAM DAN HUKUM POSITIF - Harry Permana; M. Iqbal Irham; Pagar (Judge : Jurnal Hukum, 2026)
The phenomenon of unregistered marriages is a social reality that still occurs frequently in Indonesia, especially among communities that adhere strongly to religious values. According to Islamic jurisprudence, unregistered marriages are considered valid as long as they fulfill the pillars and requirements, namely a guardian, two witnesses, and a marriage contract (ijab kabul). However, from the perspective of Indonesian positive law, specifically Marriage Law No. 1/1974 and the Compilation of Islamic Law (KHI), the validity of a marriage must be proven by official registration before a Marriage Registrar. This difference creates a legal dilemma: on the one hand, unregistered marriages are recognized religiously, but on the other hand, they have no legal force in the eyes of the state. This gives rise to various social and legal problems such as the lack of legal protection for wives and children, as well as difficulties in obtaining inheritance rights and family legal status. The purpose of this study is to analyze the relationship between unregistered marriages and their validity according to Islamic law and legal certainty according to Indonesian laws and regulations. This study uses a normative-juridical approach with a descriptive-comparative analysis method, namely comparing the provisions of Islamic law with positive law and analyzing their implications. The research results show that unregistered marriages fulfill the requirements for a valid marriage, but they do not guarantee legal certainty and protection because they are not officially registered. This situation creates potential injustice, especially for women and children born from unregistered marriages. Therefore, harmonization of Islamic law and positive law is necessary to ensure legal enforcement without neglecting the legality of the state. Marriage registration is not merely an administrative matter, but an instrument of legal protection that aligns with the principle of benefit in Islamic law.